Wisdom in Narrative: An Oral Literature Study of the Dayak Kenyah Myths in Antutan, Bulungan - Jefry Jefry; Atefeh Salemi; Obianuju Osita Oku (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to describe the functions of myths within the Dayak Kenyah community in Antutan Village and explain their cultural significance as part of the community’s oral literary tradition. Methodology: This study employed a qualitative descriptive method using human instrument techniques. Data were collected through in-depth interviews, voice recordings, direct observation, field notes, and documentation. Four native informants were selected using purposive sampling. Data were analyzed using identification, classification, interpretation, and inference procedures. Main Findings: The study identifies thirty-seven myth data classified into four main functions: projection system (five data), cultural validation (eleven data), pedagogical function (thirteen data), and social control (nine data). These myths reflect moral, social, customary, and spiritual values embedded in daily life, indicating that the Dayak Kenyah people sustain cultural identity through oral traditions and inherited beliefs. Novelty/Originality of this study: This study provides the first systematic documentation of Dayak Kenyah myths in Antutan Village, a topic that has not been previously researched. It offers new insights into the cultural logic, functions, and values of these myths, enriching oral literature studies and supporting efforts to preserve local indigenous knowledge.